El rol del diseño institucional en la aplicación de responsive regulation frente al abuso de posición dominante - Mufdi Guerra, Nader (2020)
Enforcement of prohibitions on abuse of a dominant position plays a crucial role in the proper functioning of markets. Enforcement strategies owe their success or failure depends on the possibilities and limits of the institutions in charge of their implementation. These possibilities and limits define the way in which the different institutions involved in enforcement are structured and related to each other, as well as the roles and powers with which these have been provided to fulfill their purposes.In this article, the author argues that there are important differences between the three traditional institutional models of competition law enforcement that would affect the implementation of Responsive Regulation strategies to deal with cases of abuse of dominant position. In this sense, it analyzes the enforcement regimes of the jurisdictions of Mexico, New Zealand and Chile, which are examples of such models. It also assesses whether such differences correlate in the practical dimension of enforcement and the performance of each of those enforcement regimes over the period 2013-2017. Finally, it explores the potential relationships that might exist between differences in terms of discretion and instances for collaborative solutions.